Effect of surfactants on the rainfastness of glyphosate on Clidemia hirta - Mohd Halim, Nurshahira (2016)
Clidemia hirta, a perennial shrub weed from the family of Melastomaceae can be found in many tropical regions of the world. The weed is distinct among many invasive plant species of the Malaysian because of its ability to invade anthropogenically undisturbed primary and tall secondary forests. In Malaysia, it is major pest on the oil palm and rubber plantation.Glyphosate is one of the broad-spectrum systemic herbicide that can be used to control this weed. Surfactant is often mixed with glyphosate to enhance the activity of glyphosate, improve wetting of the surface of plants for maximum coverage and aid penetration through the plant surface. However, rain shortly after herbicide application is one of the most detrimental issues for herbicide performance. The research was conducted to determine the influence of surfactants on the rainfastness of glyphosate on C.hirta. The experiment was conducted at Field 2, UPM Serdang. Glyphosate at 3 L product/ha and spray volume of 450L/ha was used together with the surfactants at recommended concentration of 0.024% for Silwet 408, 0.05% for Miracle S240, 0.1% for Kao A-134 and 0.14% BOND Adjuvant. Spraying was conducted on eight week old plants after transplanting followed by exposure to the rainfall using rainfall stimulator at 1 and 3 hours after spraying. The evaluation parameters were spray deposition, necrosis and chlorophyll content. The result was analyzed by using ANOVA and mean separation by Tukey. All treatments of glyphosate with surfactant showed better performance in killing the weeds compared with glyphosate alone. Treatment of glyphosate with Miracle S240 showed lower mean chlorophyll content and higher necrosis and spray deposition.The rain at 3 hours after spraying showed the higher spray deposition compared to 1 hour.More spray deposition was washed out at 1 hour after spraying. Miracle S240 was one of the best surfactant that improved the rainfastness of the herbicides.